Role of condom negotiation on condom use among women of reproductive age in three districts in Tanzania - Exavery Amon (BMC Public Health, 2012)
Abstract Background HIV/AIDS remains being a disease of great public health concern worldwide. In regions such as sub-Saharan Africa (SSA) where women are disproportionately infected with HIV, women are reportedly less likely capable of negotiating condom use. However, while knowledge of condom use for HIV prevention is extensive among men and women in many countries including Tanzania, evidence is limited about the role of condom negotiation on condom use among women in rural Tanzania. Methods Data originate from a cross-sectional survey of random households conducted in 2011 in Rufiji, Kilombero and Ulanga districts in Tanzania. The survey assessed health-seeking behaviour among women and children using a structured interviewer-administered questionnaire. A total of 2,614 women who were sexually experienced and aged 15-49 years were extracted from the main database for the current analysis. Linkage between condom negotiation and condom use at the last sexual intercourse was assessed using multivariate logistic regression. Results Prevalence of condom use at the last sexual intercourse was 22.2% overall, ranging from12.2% among married women to 54.9% among unmarried (single) women. Majority of the women (73.4%) reported being confident to negotiate condom use, and these women were significantly more likely than those who were not confident to have used a condom at the last sexual intercourse (OR = 3.13, 95% CI 2.22-4.41). This effect was controlled for marital status, age, education, religion, number of sexual partners, household wealth and knowledge of HIV prevention by condom use. Conclusion Confidence to negotiate condom use is a significant predictor of actual condom use among women in rural Tanzania. Women, especially unmarried ones, those in multiple partnerships or anyone needing protection should be empowered with condom negotiation skills for increased use of condoms in order to enhance their sexual and reproductive health outcomes.